An Eye for an Eye: Brian Evenson’s Merciless Art of Exposure - Jean-Yves Pellegrin (Sillages Critiques)
This paper looks into the way Brian Evenson’s “colorless writing” means to show violence in a way that leaves the reader unsheltered from it. Aiming at transparency or blankness, Evenson’s impersonal writing, though controlled and measured, introduces minimal distance between the reader and the acts of violence it depicts, as if trying to disappear behind them. Evenson’s prose thus makes a bid for the evidential power of photography and, by the same token, attempts to turn the reader’s own eye into a camera eye. The process, however, results in a form of overexposure that turns transparency into opacity and inflicts irremediable blindness on the reader – an act of violence which is ultimately aimed at language itself.